Hürmetler (Budapest)
514 sayfa
Keywords: “Pál Fodor is renowned in his own country and internationally as a scholar of Ottoman history. His works are essential reading for anyone aiming to understand the empire of the “Turks“ and how it developed at every stage. His studies on the ideology of the holy war, the selfdefinition of the Ottoman elite, stability and change in the history of the sultanate, and the empire's late-sixteenth-century financial crisis and the attempts to resolve it all display the depth of his erudition and the great breadth of his sources. He has actively participated in investigations to find the burial place of Süleyman I near Szigetvár and to locate and reconstruct the events of the Battle of Mohács in 1526. His friends and colleagues have produced this Festschrift on the occasion of his 70th birthday to express their personal gratitude and their great respect for his activity as a scholar and as an academic leader.” --